Pengaruh Media Animasi Terhadap Hasil Belajar Matematika Siswa Kelas V di SD Negeri 107393 Diski Tahun 2022/2023 - Safira, Nurul; Harahap, Syarifah Ainun; Hariati, Emy (Medan Resource Center, 2024)
This research is experimental research which aims to determine the effect of animation media on mathematics learning outcomes in spatial material. To determine the effect of animation media on conventional learning. The type of research used in this research is Quasy Experimental. The research design used in this research is nonequivalent control group design. The population in this research is all school students at SD Negeri 107393 Diski for the 2022/2023 academic year in the even semester, totaling 20 students. The data analysis technique is descriptive statistical analysis and inferential statistical analysis. Based on the results of inferential statistical test analysis using the paired sample t-test, 0.00 is smaller than 0.05. Based on the research results, it can be concluded that (1) The use of Animation Media for Class V Students at SD Negeri 107393 Disk is classified as very effective. (2) Mathematics Learning Results for Class V Students are very high. (3) There is a significant influence of the use of Animation Media on the Mathematics Learning Outcomes of Class V Students at SD Negeri 107393 Diski.